(3GdOQ GdeajO ddeSJQTO GdeQjOs
(3ChdgG (B:s
(3eYGTQ GdENhGf CjOce Gdgd CeG HYO agPG cJGH GdOQ GdeajO ddeSJQTO GdeQjO jJVef cd af ZQjH ef CMcGe fHhjg s
(3BNQgG (B:s
(3BNQ GdehLhO efg bGd dYHV CUMGUHg ai YdI GYJdgG LYd s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ , JGeI s
(3GdfSNI HgG JdhjK s
Keywords: (3GdeYGQa GdYGeIs